PERTANGGUNG JAWABAN NOTARIS DALAM PEMBUATAN AKTA BERDASARKAN PEMALSUAN DOKUMEN OLEH SALAH SATU PIHAK (STUDI PUTUSAN MAKAMAH AGUNG REPUBLIK INDONESIA NO : 385 K/PID/2006) - KHAIRUL IQBAL MARPAUNG (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. T. Keizerina Devi A3. Suprayitno A Notary as a public officialHe is not an investigator toward the deeds he has made; he only makes authentic deeds asked by the persons appearing since he is a public official. The result of the research shows that a Notary’s liability for the deeds he has made when it is based on document forgery is not completely his own liability as long as it is done according to the procedure and legal principle. The Judge’s verdict has been in accordance with the principle of justice by considering that there is an illegal act in forgery committed by a Notary in drawing up a purchase certificate of the transaction of a parcel of land. However, the act is not committed by the Notary but by one of the persons appearing who intentionally have forged the Notary’s signature.Keywords: Liability, Notary, Document Forgery